Two cases of post‐traumatic inferior vena cava thrombosis. Issue 1 (17th September 2021) - Minami, Sakura; Suzuki, Naoya; Okano, Hiromu; Mishima, Sena; Shimada, Kosuke; Umeda, Sayo; Michishita, Takahiro; Hayakawa, Sho; Otsuka, Tsuyoshi; Miyazaki, Hiroshi; Furuya, Ryosuke
Abstract : Background: Inferior vena cava thrombosis is a rare blunt abdominal trauma complication often associated with severe liver injury. We present two cases of inferior vena cava thrombosis due to mild liver injuries. Case Presentation: Case 1 was a 25‐year‐old woman taking oral contraceptives for dysmenorrhea who was injured in a motorcycle accident. Contrast‐enhanced computed tomography revealed hepatic contusion of the sixth segment. At 1 week after the accident, inferior vena cava thrombosis was detected. Case 2 was a 58‐year‐old man injured in a motorcycle accident. Contrast‐enhanced computed tomography showed traumatic subarachnoid hemorrhage, right hemothorax, and liver injury with hepatic contusion of the sixth segment. At 1 week after the accident, inferior vena cava thrombosis was observed. Conclusion: Inferior vena cava thrombosis can occur following liver injury, regardless of damage severity. When there are thrombogenic factors and damage near the inferior vena cava, follow‐up examinations should be carried out. Abstract : This work presents two cases of inferior vena cava (IVC) thrombosis due to mild liver injury and discusses current reports on this topic. To the best of our knowledge, our work is the first reporting IVC due to mild liver damage, as most reports so far linked IVC thrombosis to severe liver damage. It provides detailed information on how IVC thrombosis was identified and treated and discusses a poorly known association between the combination of mild liver damage, thrombogenic factors, and IVC thrombosis.